Cost-Based Environmental Liability Assessment of Acid Mine Drainage Management within the Integrated Geo-Hydrochemical Risk Assessment (IGHRA) Framework - Yazid Fanani; Eko Teguh Paripurno; Dwi Fitri Yudiantoro; Tedy Agung Cahyadi (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2025)
Acid mine drainage generates environmental liabilities that mining operators must translate into measurable management costs. This study assesses the cost-based environmental liability of acid mine drainage management within the Integrated Geo-Hydrochemical Risk Assessment (IGHRA) framework by linking pollution risk, treatment performance, and environmental cost into a single risk-to-cost evaluation. The study uses source characterization, mine water quality data, compliance-based risk indicators, treatment performance, and operational cost components to estimate two principal cost categories, namely restoration cost and preventive expenditure cost. Restoration cost represents the annual cost required to restore contaminated mine water until all regulated parameters comply with the applicable standard. In contrast, preventive expenditure represents the five-year cost required to suppress future acid generation from potentially acid-forming material through selective handling, temporary stockpiling, installation of compacted clay cover, and runoff control. The results show that the only CaO scenario produces the lowest treatment cost, but does not achieve full compliance because sulfate remains above the standard. The CaO 10 g/L and BaCl₂ 3.0 g/L scenario achieves full compliance and provides the most economical restoration cost among the compliant options, with an estimated value of IDR 516,463,856 per year. The total preventive expenditure cost over five years reaches IDR 3,832,950,186. At a midpoint selling price of IDR 89,000 per ton, the compliant CaO and BaCl₂ scenario exerts an environmental cost pressure of 8.58 percent on projected gross revenue. These results show that the IGHRA framework can convert acid mine drainage risk into measurable environmental liability and can support technically grounded and economically accountable mine water management.